The Metaphors Used in France Football Magazine - Laksman-Huntley, Myrna; Ahmad, Mubarik (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2025)
This article analyzes metaphors within ‘figures of speech’ that discuss the top six leagues in the UEFA rankings in a French football magazine France Football. These articles were chosen because they generated the most news items on the magazine's website and because high ratings of a respective league tended to confirm its quality. It was found that metaphors are mainly refer to 5 elements in football: 1) football players and coaches; 2) football teams; 3) football techniques; 4) football devices; 5) the circumstances that occur in football matches and that they are used to promote a deeper impression to the reader about diverse football elements as the writer highlights an element by making it appear more important than perhaps it is. The use of metaphorical expressions in football terminology becomes one of the factors that make this sport news increasingly popular. These forms of figure of speech are most often found in literary works, but it was also found that these devices are becoming increasingly important in other forms of writing for various purposes.